Trend of Gender Disparity in the Appointment of Vice-chancellors in the Nigerian Universities - Muhinat, Bello Bolanle (Faculty of Social Science, Universitas Negeri Semarang, 2021)
The study examined the trend of gender disparity in the appointment of vice-chancellor in Nigerian Universities, analyzing some factors responsible. A study adopted an ex post facto descriptive form of survey design. Eight purposively sample first and second-generation universities were sampled for the study out of 13 and a total of 1,332 staff out ofÃ‚Â 18,814 staff of the sampled universities also constituted the sampled population in the study.Ã‚Â A Ã¢â‚¬â€œ 13 items four-point-Likert scale researcherÃ¢â‚¬â„¢s designed questionnaires from the available literature with psychometrics properties of content validity and a reliability index of 0.73 were used for eliciting the needed data from the respondents. The findings revealed that since the inception of the sampled universities, males have dominated its leadership with 100%. This domination was due to no other reason but gender discrimination. It was recommended among others thatÃ‚Â females in universities should be allowed to head universities since the study revealed that they are not bad managers, they are good administrators at all other levels of the educational system in Nigeria. yet they are denied headship of universities.